Upper cervical instability associated with rheumatoid arthritis: What to 'know' and what to 'do' - Slater, Helen; Briggs, Andrew; Fary, Robyn; Chan, M. (Churchill Livingstone, 2013)
This case report describes a patient who presented with cervical spinal pain and headaches associated with atlanto-axial subluxation (AAS) secondary to rheumatoid arthritis (RA). For physiotherapists, especially less experienced clinicians, the significant risks associated with using manual assessment and treatment techniques in such a patient require careful consideration right at the start of a consultation. The focus of the case is therefore on the recognition of AAS in this patient with RA, highlighting the clinical findings that alert clinicians to this possibility and explaining the requisite knowledge and skills required to safely and effectively manage this patient. The use of screening tools to help clinicians identify possible RA in its pre-diagnosis stage and the clinical signs and symptoms that raise the index of suspicion for AAS, are discussed. The relevant contraindications and precautions associated with manual treatments directed at the upper cervical spine, and which may have potentially serious negative consequences, including quadriplegia and mortality, are addressed. Finally, the implications for the use of manual assessment and treatment of patients with RA and co-morbid AAS are addressed.